Peningkatan Minat Dan Hasil Belajar Matematika Siswa Melalui Model Pembelajaran TGT - Jannah, Afifah Miftahul; Noor, Naili Luma'ati (ILUMINASI: Journal of Research in Education, 2024)
Learning mathematics using conventional learning models results in students being less interested in learning so that students' interest in learning mathematics is low. Low interest in learning can also result in unsatisfactory learning results. This research aims to determine the TGT learning in increasing student interest and learning outcomes. The type of research used is field research with a quantitative approach. The population in this study were students of class XI MA NU Raudlatut Tholibin while the sample was taken from 1 class using the Simple Random Sampling technique. collection techniques use questionnaires and tests. The data were analyzed using statistical data techniques. The research results show that there are differences in student interest and learning outcomes between before and after learning TGT  with an interest pretest average score of 45.05 and an interest posttest score of 62.55. Meanwhile, for the N-gain test, there were 3 students in the low category with increased interest in learning, 11 students in the medium category, and 8 students in the high category. In the mathematics learning outcomes test, the average pretest score was 30.45 and the posttest score was 64.27, while for the N-gain test, there were 4 students with improved learning outcomes in the low category, 12 students in the medium category, and 6 students in the high category.